Comparing the effects of two different progesterone vaginal gels, Progeson™ and Crinone™, from pharmacokinetics study to clinical applications in patients undergone fresh embryo transfer and frozen-thawed embryo transfer via natural cycle endometrial preparation protocol - Cheng-Wei Yu; Wei-Jiun Li; Wen-Chi Hsieh; Li-Shan Chen; Yi-Ping Li (Elsevier, 2023)
Objective: The pharmacokinetics performance and clinical pregnancy rate of two vaginal progesterone gel, Progeson™ and Crinone™, were compared in this study. Materials and methods: In the pharmacokinetics performance, Progeson showed similar long-term dissolution rate as Crinone. In the clinical study, 141 subjects undergone in vitro fertilization (IVF) treatments were included to compare serum progesterone level and clinical pregnancy rates. Results: Among the subjects, 78 subjects received fresh embryo transfer and 63 subjects received frozen embryo transfer via natural cycle endometrial preparation protocol. In each group, subjects were given either Crinone™ or Progeson™ for luteal phase support without combination with other progesterone products. The study showed that Crinone™ group led to higher estrogen level at mid-luteal phase in the fresh embryo transfer group, and Progeson™ group led to higher progesterone level at mid-luteal phase and pregnancy test day in the frozen-thawed embryo transfer group. Conclusion: Subjects received Crinone™ or Progeson™ had similar rate of pregnancy, live birth, and stillbirth in both fresh embryo transfer and frozen-thawed embryo transfer group. Thus, Progeson™ might be a suitable substitute for Crinone™ in assisted reproductive therapy.